Eleanor of Aquitaine
XXIX, 506 p.
Keywords: Eleanor's patrilineal descent, from a lineage already prestigious enough to have produced an empress in the eleventh century, gave her the lordship of Aquitaine. But marriage re-emphasized her sex which, in the medieval scheme of gender-power relations relegated her to the position of Lady in relation to her Lordly husbands. In this collection, essays provide a context for Eleanor's life and further an evolving understanding of Eleanor's multifaceted career. A valuable collection on the greatest heiress of the medieval period.